Problems of urban development in the Algerian city - Triaa, Hakim; Djimli, Boubakar (Journal of Human Sciences, 2021)
Urban development in the Algerian city, alike other cities of developing countries, has known a bunch of problems, and multiple crises that contained different manifestations and dimensions on several levels: urban, legal, real estate and so forth. These problems did not come out of the blue, but they were caused by a variety of reasons.   We try in this article is address the concepts of urban development. Moreover, we seek to address the most important aspects of the urban development crises in the Algerian city, by working on analyzing the causes, and proposing a set of solutions and recommendations that can contribute to reducing the repercussions of these problems on social life in general in the Algerian city.